1977
DOI: 10.1002/mrc.1270090612
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the dibenzo [a,g]‐quinolizidines by spectroscopic means. II—The use of high resolution 270 MHz proton magnetic resonance

Abstract: The 270 MHz 'H n.m.r. spectra of some model tetrahydroprotoberberines have been analysed and the dependence of the chemical shifts and the geminal and interbenzylic coupling constants on the conformation examined. Their use for conformational analysis was illustrated on two 8-methyl substituted epimers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…For paper XXII, see Likhitwitayawuid et al (1). [1} (7,8), (-)-asimilobine-2-0^-D-glucoside [2}, (-)-anonaine [3} ( 9), (-)-isolaureline [4} (10), (-)-xylopine [5} (10), (-)-roemeroline [6} (11), (-)-dicentrine [7} (12)(13)(14), ( -)-nordicentrine [8}, ( -)-phanostenine [9} (15), cassythicine [10} (14,16), and magnoflorine [11} (17)(18)(19)(20); (b) the tetrahydroprotoberberines (-)-tetrahydropalmatine {12} (21-23), (-)-capaurine [13} (24-27), ( -)-thaicanine [14} (23), (-)-corydalmine [15} (25,26), ( -)-N-methyltetrahydropalmatine [16} (28), (-)-xylopinine [17} (22), and (-)-tetrahydrostephabine [18} (29); (c) the tetrahydrobenzylisoquinolines (+)reticuline [19} (30,31), (+)-codamine [20} (32,33), and (±)-oblongine [21} (34,35); (d) the hasubanan ( -)-delavaine [22} (36) and the morphinan (-)-salutaridine [23} (37,38). Compounds 2 and 8 are hitherto unknown alkaloids.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For paper XXII, see Likhitwitayawuid et al (1). [1} (7,8), (-)-asimilobine-2-0^-D-glucoside [2}, (-)-anonaine [3} ( 9), (-)-isolaureline [4} (10), (-)-xylopine [5} (10), (-)-roemeroline [6} (11), (-)-dicentrine [7} (12)(13)(14), ( -)-nordicentrine [8}, ( -)-phanostenine [9} (15), cassythicine [10} (14,16), and magnoflorine [11} (17)(18)(19)(20); (b) the tetrahydroprotoberberines (-)-tetrahydropalmatine {12} (21-23), (-)-capaurine [13} (24-27), ( -)-thaicanine [14} (23), (-)-corydalmine [15} (25,26), ( -)-N-methyltetrahydropalmatine [16} (28), (-)-xylopinine [17} (22), and (-)-tetrahydrostephabine [18} (29); (c) the tetrahydrobenzylisoquinolines (+)reticuline [19} (30,31), (+)-codamine [20} (32,33), and (±)-oblongine [21} (34,35); (d) the hasubanan ( -)-delavaine [22} (36) and the morphinan (-)-salutaridine [23} (37,38). Compounds 2 and 8 are hitherto unknown alkaloids.…”
Section: Resultsmentioning
confidence: 99%
“…Fractions 19 to 2 2 were pooled, dried in vacuo, and recrystallized from Me2CO to give (-)-tetrahydropalmatine [12] (8.4 g). Fraction 24 was further purified by preparative tic eluting with toluene-diethylamine (DEA) (96:4) to afford (-)-xylopinine [22] (15 mg). Fractions 25 to 31 were combined and subjected to preparative tic, using cyclohexane-EtOAc-DEA (5:4:1) as the solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further comparison of other physical properties (see Experimental section) confirmed that the isolate was indeed 4. Although portions of the 'H-nmr spectrum of 4 have been reported (16), in Table 1 we have indicated the assignment for each resonance in the 400 MHz spectrum. Determination of the optical rotation of 4 established that it was ( -)-tetrahydropalmatine with the (5) absolute configuration as depicted in Scheme 1 (17,18).…”
mentioning
confidence: 99%
“…um 10 ppm (3a-c) und 13 pprn (3g-i) gefunden werden. Charakteristisch iat die Signalfolge der Protonen in den Positionen C(5) und C (7) des heterocyclischen Sechsringes, fur den in Analogie zum Cyclohexen eine Halbsesselkonformation diskutiert werden kann. Von diesen Protonen, die aufgrund ihrer Stellung magnetisch nicht aquivalent sind, ergibt H-7ax zwischen 3,79-3,98 pprn jeweils ein leicht verbreitertes Singulett.…”
unclassified